2005
DOI: 10.1097/01.prs.0000178783.44190.ec
|View full text |Cite
|
Sign up to set email alerts
|

Guided Bone Regeneration at the Donor Site of Iliac Bone Grafts for Future Use as Autogenous Grafts

Abstract: The periosteum acted as an ideal membrane for guided bone regeneration so that the polytetrafluoroethylene membranes could be used only to compensate for the deficient periosteum. Space maintenance was essential for bone regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Theb one plate combined with titanium cage wasp artiallyw rapped with remaining periosteum, sinceinyoung sheep theperiosteum is usuallyt hicka nd easilyi dentified. Thef indingso fs ome othere xperimental studiessuggested that theperiosteumcan be consideredanatural membrane to guide bone regeneration, butitisnecessary to place some typeo fi mplant, such as our titanium cage, within the defect to preventcollapse (14,15). The latterwas represented, in the report presented herein, by the perforated titanium cage.…”
Section: Discussionsupporting
confidence: 49%
“…Theb one plate combined with titanium cage wasp artiallyw rapped with remaining periosteum, sinceinyoung sheep theperiosteum is usuallyt hicka nd easilyi dentified. Thef indingso fs ome othere xperimental studiessuggested that theperiosteumcan be consideredanatural membrane to guide bone regeneration, butitisnecessary to place some typeo fi mplant, such as our titanium cage, within the defect to preventcollapse (14,15). The latterwas represented, in the report presented herein, by the perforated titanium cage.…”
Section: Discussionsupporting
confidence: 49%
“…The no need for a barrier membrane in the proposed protocol significantly reduced the surgical time and cost and may be attributed to enhanced bone regeneration as the periosteum was not isolated from the grafted site. Periosteum has been shown to play a pivotal role in bone graft incorporation, healing, and remodeling, as it contains multipotent mesenchymal stem cells that are capable of differentiating into bone and cartilage and provides a source of blood vessels and growth factors [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there was soft tissue ingrowth, which probably explains why less bone was generated. Other studies have shown that an occlusive barrier can be negative factor in bone healing and that perforated material is preferable to allow the periosteum to play a part in the initial mineralization and remodelling of the grafted area (Elshahat et al 2005; Zhang et al 2008). In contrast, a rabbit study has shown that membrane permeability is not essential in guided generation of new bone (Schmid et al 1994).…”
Section: Discussionmentioning
confidence: 99%